Engineering materials : properties and selection. - Budinski, Kenneth G., 1939-; Budinski, Michael R., ....- (Upper Saddle River : Pearson, 2010)
This text covers theory and industry-standard selection practices, providing students with the working knowledge to make an informed selection of materials for engineering applications and to correctly specify materials on drawings and purchasing documents. Encompassing all significant material systems-metals, ceramics, plastics, and composites-this text incorporates the most up-to-date information on material usage and availability, addresses the increasingly global nature of the field, and reflects the suggestions of numerous adopters of previous editions. For undergraduate courses in Metallurgy and Materials Science